Coping with English at tertiary level : instructors’ views - Hafdís Ingvarsdóttir 1944-; Birna Arnbjörnsdóttir 1952- (2010)
Over 90% of the curriculum material at the University of England is in English. The purpose of the current research project is to explore views of university instructors on how this extensive use of English course material affects their instruction and students’ learning. Data was collected through electronic surveys to all instructors at the University of Iceland. The questions asked were: How do Icelandic university instructors’ perceive their own proficiency in English and their ability to cope? Is there a difference between academic fields in instructors’ views of the use of English? Do instructors use scaffolding devices to help their students cope; which and how? The findings indicate that most instructors in the survey rate their Eng-lish proficiency as very good although they need help with their academic writing. Although the study also suggests that instructors believe that using English curriculum material causes few or no problems to their students, many of them feel they need to use a variety of scaffolding devices to support their students’ learning. Um 90% kennsluefnis við íslenska háskóla er skrifað á ensku. Markmið rannsóknarinnar sem hér er fjallað um var að kanna viðhorf kennara við Háskóla Íslands til notkunar námsefnis á ensku. Kannanir voru sendar til allra kennara við Háskóla Íslands og þeir spurðir: 1.Hvernig meta kennarar eigin enskukunnáttu og hæfnina til að nota ensku? 2. Er munur á viðhorfum kennara til enskunnar eftir sviðum? 3. Nota kennarar stoðir til stuðnings fyrir nemendur, þá hvaða og hvernig? Niðurstöðurnar benda til að að kennarar telji enskukunnáttu sína mjög góða eða góða en margir þurfa aðstoð við greinaskrif á ensku. Rann-sóknin bendir einnig til að þrátt fyrir að kennarar telji að nemendur ráði vel við enskuna finnst mörgum að þeir þurfi að nota ýmsar aðferðir til að styðja nem-endur við að tileinka sér námsefnið.